Study power of partial discharges to voltage intensity in XLPE-insulated cables - D. A. Polyakov; K. I. Nikitin; N. A. Tereschenko; I. V. Komarov; U. V. Polyakova (Омский научный вестник)
The article investigates partial discharges (PD) as a mechanism of insulation destruction. Some of the known mathematical models of insulation aging take into account the effect of partial discharges. These models are based on the dependence of partial discharges power on voltage, so this dependence is investigated in the article. Experimental studies of the dependence of the characteristics of partial discharges are presented. As a source of an increased level of partial discharges, a defect is used in the termination area of the 10 kV cable with XLPE insulation. The voltage range of experiments is from 8 to 15 kV. The results show the presence of a dangerous defect in the cable. Partial discharges at 8 kV are insignificant. However, 10 kV leads to the appearance of significant partial discharges. PD at 15 kV have the most devastating effect on insulation. The results are processed to assess the dependence of PD power on voltage. The resulting dependence is consistent with existing research results. However, the obtained characteristics may change over time due to the growth of the defect.